Human Development E-Learning System - Wong, Shing Fei (2007)
This study highlights the elements of research heve been done on the e-learning based on the learners' view and instructor's view on the learning system to help in developing the Human Development e-Learning System. These research focus on paying attention to the meaningful opportunities for learners reflection and educator reflection and educator reflection on the learning system, considering appropriate technologies and criteria needed for system delivery, ensuring that the design is suitable for the context in which it will be used , and bearing in mind the impact of the designed activities.